On the Composition Ideals of Schatten Class Type Mappings. (14th August 2016) - Belaada, Abdelaziz; Saadi, Khalil; Tiaiba, Abdelmoumen
Abstract : We study the composition ideals of multilinear and polynomial mappings generated by Schatten classes. We give some coincidence theorems for Cohen strongly 2-summing multilinear operators and factorization results like that given by Lindenstrauss-Pełczński for Hilbert Schmidt linear operators.